O uso de dispositivos móveis no processo de produção de notícias: um estudo de caso na Rádio Independente 950 AM de Lajeado/RS - Gomes, Rafael de Jesus (2015)
This dissertation aims to understand what is the role that journalists attribute to mobile devices in their production routines. The role of the professional in contemporary journalism field experiments the inclusion of digital technologies to the news production. A possible feature that can be considered is the mobility (SILVA, 2008), allowing the professional the possibility to carry its device to the information production. Among the Technologies, stands out the tablet. According to Canavilhas (2012), it is a tool that provides the journalist the possibility of narratives construction that, currently, it's updating the journalism language, becoming the position of the new Swiss Army Knife (JENKINS, 2008). To the radio, the addition of this tools also expands its mains features and allows to think of a radio that it is now expanded (KISCHINHEVSKY, 2011) in multiple plataforms, digital social networks and applicatives. Considering that the technologies and mobile devices updates the process of production of news, and the content consumption, this scenario is only possible from the influence of the convergence at the newsroom, this work aims to discuss how, actually, this devices are being used to the productions of news by the professionals and recognize the potentialities that it can be offered and used by the journalists. Therefore, this work seeks to understand how journalists use this tools in their work and how it reflects the news production in a radio station. As a research subject, it is chosen the Radio Independente 950 AM, from Lajeado/RS. As a methodological procedure, it was made a literature review about the following themes: radio, the convergence, professional culture, and the digital features to the news production. The collect tools used on this research was the observation and interviews. The interviews were the main tool and it was collected eleven statements with the newsroom professionals, production, web department and administrative department of the radio, as well as the observation of the routine productions in the radio.